Community Empowerment Through the Rasa Guna Group Program to Improve Self-Care - Shafa Okta Salsabila; Aghiva Digvha Arryana; Qonita Qonita; Alif Nuariyanto; Astinda Zian Pusparina; Amalya Rosita Omadi; Helsa Juwinda Erlanni; Muhammad Raffi Habibi; Anisa Anggun Kinasih; Syayidiahtun Ihda Nur Baeti; Anas Indratanaya; Arif Budiman; Alfato Yusnar Kharismasyah (Proceedings Series on Social Sciences & Humanities, 2025)
Stable mental health relate close with health physical and quality life. Arisan Rasa is innovation a community that combines regular meetings, sharing experience and education self-care in harmony culture local. This program give knowledge as well as moral and social support, encouraging Mother House stairs in Legoksayem Village For consistent apply self-care approach This become step beginning form a healthy, caring, and independent community. Participants consists of of 28 women age productive (35–45 years) with background education diverse and majority profession as Mother House stairs. The method used is experiment pseudo with design one group pre –post test desig . Analysis results using the Wilcoxon Signed Ranks Test shows existence improvement significant on the total value of participants after intervention (Z = -4.250; p = 0.000), which indicates difference meaningful between score pre-test and post-test. Evaluation through observation and interviews support findings this, with majority participant report improvement knowledge, skills, and habits self-care. This program proven give impact positive to empowerment society and can become an intervention model health at the level village. Awareness that self-care is investment for welfare self and family become key change behavior. Sustainability practice This need support community, family, and government villages so that self-care becomes part style live, impact positive on health physical, mental, and quality life.